Orexin supplementation in narcolepsy treatment: A review. Issue 3 (14th November 2018) - Nepovimova, Eugenie; Janockova, Jana; Misik, Jan; Kubik, Stepan; Stuchlik, Ales; Vales, Karel; Korabecny, Jan; Mezeiova, Eva; Dolezal, Rafael; Soukup, Ondrej; Kobrlova, Tereza; Pham, Ngoc Lam; et al.
Abstract: Narcolepsy is a rare, chronic neurological disease characterized by excessive daytime sleepiness, cataplexy, vivid hallucinations, and sleep paralysis. Narcolepsy occurs in approximately 1 of 3000 people, affecting mainly adolescents aged 15 to 30 years. Recently, people with narcolepsy were shown to exhibit extensive orexin/hypocretin neuronal loss. The orexin system regulates sleep/wake control via complex interactions with monoaminergic, cholinergic and GABA‐ergic neuronal systems. Currently, no cure for narcolepsy exists, but some symptoms can be controlled with medication (eg, stimulants, antidepressants, etc). Orexin supplementation represents a more sophisticated way to treat narcolepsy because it addresses the underlying cause of the disease and not just the symptoms. Research on orexin supplementation in the treatment of sleep disorders has strongly increased over the past two decades. This review focuses on a brief description of narcolepsy, the mechanisms by which the orexin system regulates sleep/wake cycles, and finally, possible therapeutic options based on orexin supplementation in animal models and patients with narcolepsy.